Professionals with borders: The relationship between mobility and transnationalism in global firms. Issue 91 (May 2018) - Spence, Crawford; Sturdy, Andrew; Carter, Chris
Abstract: Recent claims assert that the transnational has displaced the national in importance vis-à-vis the governance of international professional organizations. Crucial to such claims are assumptions about rising geographical mobility and the emergence of cosmopolitan professionals who are increasingly detached from national professional regimes and contexts. We interrogate claims about the importance of transnational spaces through a cross-national study of global professional service firms in 12 countries. Our study demonstrates how the imperatives of client service, the locally rooted nature of social capital and cultural barriers all contrive to limit the ability and necessity of professionals to move across borders in their work and the pursuit of successful careers. The vitality of transnational firms appears to depend on professionals who are, for the most part, locally groomed – professionals with borders - who may only experience one short period of limited geographical mobility, usually early in their careers. Where transnational mobility is in evidence, it tends to take a more virtual than physical form. These results temper arguments about the rise and, certainly, extent of, physical mobility among elite employees of global professional service firms and, in turn, about the extent to which the transnational has supplanted the national as the most important frame of reference for professional organization. Rather, they support views that see the transnational and local as co-existing and interconnected.